Technical facilities available for the speech and hearing handicapped in hospitals in India-a survey - Ashish Kumar Purwar (Journal of All India Institute of Speech and Hearing, 1970)
The survey was designed to determine the personnel, equippment and technical facilities available in the field of Speech and Hearing in hospitals in India. The type of equipment manufactured in the field of Speech and Hearing in India was also investigated.